Genre Classification and the Current State of Turkmen Musical Folklore - Джаміля Курбанова (Культура і мистецтво у сучасному світі)
The aim of the article is to characterise the existing classification systems of Turkmen musical folklore, as well as to outline new ways of studying folklore genres to determine their typological characteristics. Results. Turkmen music is part of a single common Turkic culture, and its musical folklore is distinguished by a variety of genres and forms. Having studied the currently available systems for classifying the musical folklore genres, the author suggests classifying Turkmen folk songs not only based on their functional features but also by grouping them by timbre and methods of sound production. Scientific novelty. The study of folklore heritage allows us to penetrate into the deep layers of the artistic consciousness of the people and identify the features of their spiritual life. The issues of studying the musical heritage of the Turkic peoples are the focus of attention of many researchers, who agree that the formation of folk genres of Turkmen music, as well as the entire Turkic culture, is based on the life cycle, with its gradation by age (children, adolescents, adults), whose attitude reflects the corresponding genres of musical folklore. Conclusions. In the modern space, it is almost impossible to find examples of genuine folklore in its purest form. The change in the forms of human life, social formations, the development of professional arts, the departure from applied functions, and the oral method of transmitting traditions — all this led to the inevitable modification and disappearance of many genres of folklore. In such a situation, the study of folklore and the search for its origins become an important task for contemporary folklore studies. The multi-layered expressive means of folklore heritage requires an integrated approach to its study, taking into account the analysis of timbre and intonation, words and rhythm, melody and general compositional structure, as well as the technique of performing folk art samples.